Gospel and Contextualization: A Case Study of St. Stephen’s Church, HKSKH - CHEN, Ruiwen (Journal of Research for Christianity in China (JRCC), 2023)
In 1865, the first Bishop of Victoria George Smith (1815-1871) established St. Stephen’s Church (parish) on Hollywood Road. This in effect is the beginning of the Chinese Anglican mission in Hong Kong. Unlike the English-speaking St. John’s Cathedral which symbolizes the presence of the Anglicanism in Hong Kong, St. Stephen’s Church was established to propagate the Gospel to the local people, and thus expresses a persistent evangelical character. Since this earliest community of faith in Hong Kong is part of the history of the Diocese of Victoria and of the Church Missionary Society (CMS), an examination of its early history will help us to clarify several questions: Under what external circumstances was this Chinese Anglican parish founded? Who were the earliest Chinese clergy and congregations? What did the early worship look like? What were the missionary strategies and acceptance levels in the 19th century Hong Kong? How did the Chinese Anglican Church interact with Hong Kong society? All of these questions may be answered, to some extent, in the early history of St. Stephen’s, which will help us understand the issue about gospel and contextualization.